Pengaruh Kualitas Produk Dan Harga Terhadap Loyalitas Konsumen Pada Logikaa Coffee House Kabupaten Toraja Utara - Junita Bungin; Chrismesi Pagiu; Randi Tangdialla (Journal Economic Excellence Ibnu Sina, 2023)
The purpose of this study was to determine the effect of product quality and price on consumer loyalty at Logikaa Caffee House. Data were collected by Questionnaire and Documentation. Data were analyzed quantitatively with multiple linear regression. The sample used in this study consistof 95 respondents. T table (1.985), shows that product quality has no effect on consumer loyalty and Price Test Results on consumer loyalty T count (4.118 > T table (1.985), shows that product quality has no effect on consumer loyalty, price has an effect on consumer loyalty The results of the F test obtained a calculated F value of 16.610 with an F table of 1.985 showing that product quality and price influence consumer loyalty simultaneously.